2021
DOI: 10.1128/mbio.03400-20
|View full text |Cite
|
Sign up to set email alerts
|

A Streptococcus Quorum Sensing System Enables Suppression of Innate Immunity

Abstract: Some bacterial pathogens utilize cell-cell communication systems, such as quorum sensing (QS), to coordinate genetic programs during host colonization and infection. The human-restricted pathosymbiont Streptococcus pyogenes (group A streptococcus [GAS]) uses the Rgg2/Rgg3 QS system to modify the bacterial surface, enabling biofilm formation and lysozyme resistance. Here, we demonstrate that innate immune cell responses to GAS are substantially altered by the QS status of the bacteria. We found that macrophage … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 42 publications
2
27
0
Order By: Relevance
“…al , 2022, submitted). stcA is associated with enhanced lysozyme resistance and biofilm formation, whereas spy49_0450-0460 is required for QS-induced immune suppression (5, 9, 14).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…al , 2022, submitted). stcA is associated with enhanced lysozyme resistance and biofilm formation, whereas spy49_0450-0460 is required for QS-induced immune suppression (5, 9, 14).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic programs that regulate virulence attributes of GAS are responsive to the microorganism's environment, and its metabolic status, through intercellular signaling networks. Quorum sensing (QS), a form of intercellular communication, is used by GAS to regulate gene expression in response to molecular signals produced by bacteria (5)(6)(7)(8)(9)(10)(11). QS activity is often coupled to the status of the environment, where characteristics such as nutrient availability or pH can impact expression or action of QS-centric genes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A PHYRE search using the GAS amino acid sequence revealed structural matches to other MFS proteins including the human iron export protein ferroportin-1, the bacilysin/siderophore transporter BacE, and the lipoteichoic acid flippase LtaA 24 . The former two hits are potentially interesting given that we previously observed that Rgg2/3 signaling is induced under conditions of iron limitation 3 and spy49_0460 is located at the end of a BGC, and the latter is interesting due to the possibility that the BCG produces a factor that alters the GAS cell surface and its subsequent interactions with macrophages 6 . However, we have not found a role for the BGC in iron uptake or a role for Spy49_0460 specifically in macrophage suppression to date.…”
Section: Discussionmentioning
confidence: 99%
“…Four types of quorum-sensing systems have been described for GAS: Sil, lantibiotic systems, LuxS/AI-2, and regulator gene of glucosyltransferase (Rgg) systems 2 . Of the latter, GAS possess four Rgg-type transcription factors which interact with small oligopeptide pheromones to control three discrete regulons: RopB (Rgg1) mediates expression of the SpeB cysteine protease, a well-characterized virulence factor; ComR (Rgg4) is implicated in natural competence; and Rgg2 and Rgg3 together regulate genes linked to cell aggregation, biofilm formation, lysozyme resistance, nasopharyngeal colonization, pharyngitis and macrophage immunosuppression [3][4][5][6][7][8][9][10] . The Rgg2/3 system is unique in that the two homologous regulators recognize the same pheromones (short hydrophobic peptides 2 and 3; SHP2 and SHP3) yet exert opposing effects on the same gene targets.…”
Section: Introductionmentioning
confidence: 99%